Growth performance and meat quality of broiler chickens fed with different levels of fermented palm kernel cake - Mohd Asri, Muhamad Faisal (2016)
Palm Kernel Cake (PKC) commonly found in Malaysia and has been categorized as agricultural by-product (ABP). PKC is widely used as ruminant feed in feed formulation. However, PKC is not very suitable for poultry due to its high fiber content. Solid State Fermentation (SSF) can help to degrade the crude fiber by using fermentation of PKC with selected bacteria. The objective of this work was to study the effect of feeding different levels of fermented PKC on growth performance and meat quality of broilers chicken from day old until 42 days of age. Birds were offered with starter and grower diets. All the chickens were fed with commercial diet for their starter period, whereas grower diet was offered from weeks 4 to 6 with different levels of PKC and Fermented PKC. The birds were distributed in a completely randomized experimental design with 9 treatments and 6 replicates. Each replicate consisted of 5 birds. PKC and fermented PKC were mixed in the diet of the birds according to the recommended nutrient requirements. All the birds were allocated to the following treatments: Treatment 1 (control), Treatment 2 (5% of PKC), Treatment 3 (10% of PKC), Treatment 4 (15% of PKC), Treatment 5 (20% of PKC), Treatment 6 (5% of Fermented PKC), Treatment 7 (10% of Fermented PKC), Treatment 8 (15% of Fermented PKC) and Treatment 9 (20% of Fermented PKC). No significant differences (P>0.05) were found between the Treatments 1, 2 and 5 on their weight gain and feed conversion ratio but Treatments 7, 6 and 5 was significant lower (Pr>0.05) compared to another treatment. For water holding capacity, Treatment 5 were found higher while Treatment 2 were found the lowest reading compared to other treatments for cooking loss. While in drip loss Treatment 1 was significantly higher (Pr>0.05) compared to other treatment. Treatment 5 and Treatment 9 were significant higher in pH value while the meat temperature showing no significant different to each other. For the meat color, the L* from treatment 2 and Treatment 5 were not significant compared to each other, while A* for Treatment 6, Treatment 3, Treatment 8 and Treatment 7 were slightly lower value compared to another treatment. For B* Treatment 3 showing the highest reading and Treatment 7, Treatment 8 and Treatment 9 were slightly significant different. In conclusion, fermented PKC can promotes growth performances and enhances the meat quality of broiler chickens at certain percentages given especially in Treatment 7 inclusion of 15% of fermented PKC. Further studies to evaluate the growth performances of broiler chicken by increment of higher level Fermented Palm Kernel Cake in feed is recommended.